Index waist size a visceral obesity marker related to non-complicated cystitis - Roque Quezada, Ezequiel (2019)
Objective: The aim of this study was to determine the association betweenwaist to height ratio and uncomplicated cystitis in a primary health care center in Lima, during the year 2018. Methods: We conducted an observational, analytical, case-control study, in which a total of 131 cases and 131 controls were obtained by simple random sample, applying exclusion and inclusion criteria. Retrospective recollection of the data was performed using the medical record of each selected patient. Odds ratio was calculated to measure the strength of association. Results: the waist to height ratio mean for uncomplicated cystitis was 61,9 ± 6.39 and 58.12 ± 3.87 for the controls. We found an statistical significant association between uncomplicated cystitis and waist to height ratio (OR 5,27; 95%CI 3,10 – 8,95; p <0,001). Waist circumference (OR 2,11 95%CI;1,26 – 3,55; p=0,005) and body mass index (OR 2,02; 95%CI 1,20 – 3,37; p=0,007) were also associated. Conclusion: we found a strong association between waist to height ratio and uncomplicated cystitis, prospective studies are suggested to confirm the association between visceral obesity and the appearance of urinary tract infections